Relevante Nebenbefunde im CT: ein unterschätzter Aspekt der modernen Lungenemboliediagnostik = Relevant secondary findings in CT - Grüttner, Joachim; Viergutz, Tim; Henzler, Thomas; Janssen, Sonja; Walter, Thomas (Notfall & Rettungsmedizin, 2015)
Background: Reliable detection of pulmonary embolism (PE) is considered a major challenge for emergency facilities. The 2008 published and 2014 updated ESC guidelines for PE recommend a strategy of low-threshold CT indication with a high proportion of examinations to exclude PE. Methods: The cases of 492 patients with suspected PE were retrospectively analyzed with regard to the incidence of secondary findings in the CT. Secondary findings were assessed in order to evaluate possible benefits of the CT scan for the patients in addition to the PE diagnostics. Results: In 59 out of 492 patients PE was detected; in 203 of these patients (41 %) secondary findings were identified. Goiter, pleural effusion, infiltration suspected of pneumonia, tumor suspected of neoplasia, and enlarged lymph nodes were particularly frequent. Pulmonal congestion, pericardial effusion, rib fracture, and pneumothorax were rare. Conclusions: Our data show a high proportion of secondary findings in the context of CT diagnostics in patients with suspected pulmonary embolism. The prognostic value of these findings varies. Only a part of these findings would have been detectable by alternative diagnostic methods. Generally, the additional information gained by secondary findings in CT seems to be useful in order to identify further examinations in addition to PE diagnostics.